Phase II evaluation of sensitivity and specificity of PCR and NASBA followed by oligochromatography for diagnosis of human African trypanosomiasis in clinical samples from D.R. Congo and Uganda. - Enock Matovu; Claire M Mugasa; Rosine Ali Ekangu; Stijn Deborggraeve; George W Lubega; Thierry Laurent; Gerard J Schoone; Henk D Schallig; Philippe Büscher (Public Library of Science (PLoS), 2010)
BACKGROUND: The polymerase chain reaction (PCR) and nucleic acid sequence-based amplification (NASBA) have been recently modified by coupling to oligochromatography (OC) for easy and fast visualisation of products. In this study we evaluate the sensitivity and specificity of the PCR-OC and NASBA-OC for diagnosis of Trypanosoma brucei gambiense and Trypanosoma brucei rhodesiense human African trypanosomiasis (HAT). METHODOLOGY AND RESULTS: Both tests were evaluated in a case-control design on 143 HAT patients and 187 endemic controls from the Democratic Republic of Congo (DRC) and Uganda. The overall sensitivity of PCR-OC was 81.8% and the specificity was 96.8%. The PCR-OC showed a sensitivity and specificity of 82.4% and 99.2% on the specimens from DRC and 81.3% and 92.3% on those from Uganda. NASBA-OC yielded an overall sensitivity of 90.2%, and a specificity of 98.9%. The sensitivity and specificity of NASBA-OC on the specimens from DRC was 97.1% and 99.2%, respectively. On the specimens from Uganda we observed a sensitivity of 84.0% and a specificity of 98.5%. CONCLUSIONS/SIGNIFICANCE: The tests showed good sensitivity and specificity for the T. b. gambiense HAT in DRC but rather a low sensitivity for T. b. rhodesiense HAT in Uganda.